A challenging and rewarding time: The early days of graduate medical education in dermatology. (August 2019) - Cocks, Margaret Maria
Specialized residency training was still in its infancy in mid-20th century America. While specialty boards in various fields such as ophthalmology and otolaryngology had been established in the 1920s and 1930s, the details of training programs were still being fine-tuned and formal curricula were lacking. In dermatology, three prominent physicians including Harry L. Arnold Jr., J. Lamar Callaway and Walter B. Shelley trained during these experimental days of medical education. Each of them captured personal reflections of their own training experiences in brief memoirs published in scientific journals. A closer examination of these texts provides unique insights into how dermatology subspecialty training in particular and medical education more broadly evolved during this period.